2015
DOI: 10.1039/c4cp05447d
|View full text |Cite
|
Sign up to set email alerts
|

First principles characterization of silicate sites in clay surfaces

Abstract: Aluminosilicate clays like Montmorillonite (MMT) and Muscovite Mica (MT) have siloxane cavities on the basal plane. The hydroxyl groups localized in these cavities and van der Waals (vdW) forces contribute significantly to adsorption processes. However, the basal sites are found to be difficult to characterize experimentally. Here, (001) surfaces of MMT and MT clays were investigated using first-principles calculations to understand how these silicate surface sites are influenced by hydroxyl groups and the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 63 publications
(88 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, the sample surface to be probed is a silicate sheet obtained from the exfoliation 5,75 of aluminosilicates like montmorillonite (MMT) clays in the surface (001). In our previous work, 7 we simulated the topographic NC-AFM image of the MMT surface using an implicit tip of silicon nitride. As described by Chan et al, 45 the force F ts was calculated by the first-principles potential with a fictitious tip.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the sample surface to be probed is a silicate sheet obtained from the exfoliation 5,75 of aluminosilicates like montmorillonite (MMT) clays in the surface (001). In our previous work, 7 we simulated the topographic NC-AFM image of the MMT surface using an implicit tip of silicon nitride. As described by Chan et al, 45 the force F ts was calculated by the first-principles potential with a fictitious tip.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, vdW-DF is necessary to better describe the layered structure of the montmorillonite (MMT). 7 On the basis of our surface characterization work, 7 we showed the presence of two types of basal oxygen sites (O1 and O2 in Figure 1A) that may be differently affected by vdW forces and/or the chemical environment of the hydroxyl groups (O3 in Figure 1A). Although the structural hydroxyl groups O3 are in the siloxane cavity, surface characterization also brings out that the oxygen sites O1 and O2 are affected by those sites in a hydrophilic way.…”
Section: Computational Proceduresmentioning
confidence: 97%
“…In particular, the distance-dependent measurement of tip/sample forces can reveal the chemical activity at the surface sites. This technique has also been employed to investigate the silicate surface properties and how the inner chemical environment can influence the outer atom due to the mineral hydroxyl groups and the ionic substitutions (Alvim and Miranda 2015). Such studies contributed to understanding how chemical additives can affect the interaction between the solid surface and the fluids phases, such as the organic functional groups in hydrocarbons in the oil, and the ions in the brine.…”
Section: Electronic Structure Levelmentioning
confidence: 99%
“…It is worthy to note that whenever treating the vdW interactions the lattice lengths were slightly contracted compared to those obtained by LDA or GGA only. 2 Although it was found that the Al-Si model is slightly lower in energetics than the Al-Al model with ∼ 0.1 eV/cell energy difference, we will use these two models for further investigation of interlayer cation exchange to consider the different local environments around interlayer cation. Table 1 Optimized lattice parameters and unit cell volume V 0 of pre-exchanged muscovite models within LDA and GGA with and without DFT-D2 dispersion correction.…”
Section: Structural Propertiesmentioning
confidence: 99%